(untitled) (Jurnal Prima Manajemen, 2025)
Corporate Social Responsibility (CSR) or Social and Environmental Responsibility (TJSL) is a corporate obligation regulated under Law Number 40 of 2007, aimed at supporting sustainable economic development and improving the welfare of communities surrounding company operations. Pelalawan Regency, characterized by high industrial activity, provides an important context for examining CSR implementation. This paper aims to analyze the alignment of CSR programs implemented by companies in Pelalawan Regency with the seven core subjects of ISO 26000, as well as to examine their implications for local social and economic development.This study adopts a qualitative approach using descriptive analysis, based on a review of previous research articles, policy documents, and online publications discussing CSR programs of PT Riau Andalan Pulp and Paper, PT Sari Lembah Subur, and PT Energi Mega Persada Bentu Limited. The analysis links corporate CSR initiatives to ISO 26000 principles and regional statistical indicators, including population dynamics, poverty levels, and small business development.The findings indicate that CSR programs implemented by the companies address several key ISO 26000 dimensions, particularly community development, environmental protection, education, health, and economic empowerment. PT RAPP and PT SLS are supported by sustainability certifications that serve as formal indicators of partial compliance with ISO 26000 principles, while PT EMP demonstrates CSR commitment through social initiatives without formal certification. However, the overall impact of CSR on improving community welfare remains limited and uneven, highlighting the need for more community-based CSR planning and structured sustainability evaluation.